2001
DOI: 10.1126/science.1060781
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Histone H4 at Arginine 3 Facilitating Transcriptional Activation by Nuclear Hormone Receptor

Abstract: Acetylation of core histone tails plays a fundamental role in transcription regulation. In addition to acetylation, other posttranslational modifications, such as phosphorylation and methylation, occur in core histone tails. Here, we report the purification, molecular identification, and functional characterization of a histone H4-specific methyltransferase PRMT1, a protein arginine methyltransferase. PRMT1 specifically methylates arginine 3 (Arg 3) of H4 in vitro and in vivo. Methylation of Arg 3 by PRMT1 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
607
2
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 691 publications
(664 citation statements)
references
References 18 publications
27
607
2
7
Order By: Relevance
“…There are three related 160-kDa proteins, SRC-1 (steroid receptor co-activator-1), TIF-2 (transcriptional intermediary factor) and RAC3 (receptor-associated co-activator-3), encoded by separate genes, which form the SRC or p160 family of co-activators (Xu and Qingtian, 2003). The molecular mechanism by which co-activators exert the chromatin remodeling and transcriptional activation involves the histone acetyltransferase activity that SRC-1 and RAC3 have at their C-terminal domain (Spencer et al, 1997;Glass and Rosenfeld, 2000) such as the recruitment of other general co-activators with enzymatic activity like CBP (CREB-binding protein)/p300, p/CAF, CARM-1 and PRMT1 (Chen et al, 1999;Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There are three related 160-kDa proteins, SRC-1 (steroid receptor co-activator-1), TIF-2 (transcriptional intermediary factor) and RAC3 (receptor-associated co-activator-3), encoded by separate genes, which form the SRC or p160 family of co-activators (Xu and Qingtian, 2003). The molecular mechanism by which co-activators exert the chromatin remodeling and transcriptional activation involves the histone acetyltransferase activity that SRC-1 and RAC3 have at their C-terminal domain (Spencer et al, 1997;Glass and Rosenfeld, 2000) such as the recruitment of other general co-activators with enzymatic activity like CBP (CREB-binding protein)/p300, p/CAF, CARM-1 and PRMT1 (Chen et al, 1999;Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…phosphate, acetyl, or methyl) to specific amino acid residues (1), which play important roles in regulating gene expression, modifying protein functions, and modulating protein-protein interactions (2)(3)(4)(5)(6). With the development of mass spectrometry (MS) techniques, increasing number of PTM sites have been identified (7,8).…”
mentioning
confidence: 99%
“…Thereinto, PRMT1, belonging to type I enzymes, participates in a variety of cellular processes including signal transduction, epigenetic regulation, and DNA repair pathways (11,12). PRMT1, on the one hand, can catalyze the methylation of histones H4 at arginine 3 (H4R3), which acts as a part of the histone code to regulate gene expression (11)(12)(13); on the other hand, recent studies have revealed that a plethora of proteins with methylated arginine residues catalyzed by PRMT1 implicate in a variety of cellular processes. For example, PRMT1 enhances gene transcription by methylating N-terminal arginine residues in NFAT-interacting protein 45, which heterodimerizes with NFAT and then enhances NFAT, driving cytokine production upon TCR signaling of T cells (14,15).…”
mentioning
confidence: 99%